Answer:
x=-5 y=3
Explanation:
-6(6x+9y=-3)
6(6x+5y=9)
(YOU HAVE TO MAKE ONE OF THE EQUATIONS NEGATIVE AND THE OTHER POSITIVE)
-36x-54y=18
36x+30y=54
(THE 36'S CANCEL OUT AND YOU ADD IT ALL TOGETHER)
-24y=72
(DIVIDE BOTH SIDES BY -24 AND IT THE LEFT SIDE CANCELS OUT)
y=3
(PUT THE 3 BACK INTO ONE OF THE EQUATIONS NOW THAT YOU KNOW THAT Y=3 BECAUSE NOW YOU HAVE TO FIND X [IT DOESN'T MATTER WHICH ONE])
6x+9(3)=-3
(MULTIPLY 9 AND 3)
6x+27=-3
(SUBTRACT 27 ON BOTH SIDES SO IT CANCELS OUT ON THE LEFT SIDE)
6x=-30
(DIVIDE BOTH SIDES BY 6)
x=-5